2021
DOI: 10.3390/jof7070565
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Genotypic and Environmental Effects on Endophyte Communities of Fraxinus (Ash) Using Culture Dependent and Independent DNA Sequencing

Abstract: Fraxinus excelsior populations are in decline due to the ash dieback disease Hymenoscyphus fraxineus. It is important to understand genotypic and environmental effects on its fungal microbiome to develop disease management strategies. To do this, we used culture dependent and culture independent approaches to characterize endophyte material from contrasting ash provenances, environments, and tissues (leaves, roots, seeds). Endophytes were isolated and identified using nrITS, LSU, or tef DNA loci in the culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
4
9
0
Order By: Relevance
“…Most frequently isolated fungi from leaves were A. alternata , Aureobasidium pullulans , Apiospora montagnei , and G. avenacea . The fungal taxa detected in shoots and leaves of F. excelsior were similar to those reported in numerous other culture-based studies [ 11 , 12 , 13 , 14 ]. However, high-throughput sequencing of the shoot and leave samples collected in the present study revealed a very contrasting fungal community structure [ 15 ].…”
Section: Resultssupporting
confidence: 86%
“…Most frequently isolated fungi from leaves were A. alternata , Aureobasidium pullulans , Apiospora montagnei , and G. avenacea . The fungal taxa detected in shoots and leaves of F. excelsior were similar to those reported in numerous other culture-based studies [ 11 , 12 , 13 , 14 ]. However, high-throughput sequencing of the shoot and leave samples collected in the present study revealed a very contrasting fungal community structure [ 15 ].…”
Section: Resultssupporting
confidence: 86%
“…A weakened tree can also become vulnerable to more severe threats, such as ash dieback disease caused by the fungus Hymenoscyphus fraxineus [22]. Ash dieback is already present on the island of Ireland and it is a major threat to the ash tree population [23]. The combination of ash dieback Adult sawflies have been seen clinging to clothing of cyclists and walkers on the Lagan towpath in Belfast and it is plausible that they could be carried on sheltered parts of cars and lorries in the same manner.…”
Section: Discussionmentioning
confidence: 99%
“…A weakened tree can also become vulnerable to more severe threats, such as ash dieback disease caused by the fungus Hymenoscyphus fraxineus [22]. Ash dieback is already present on the island of Ireland and it is a major threat to the ash tree population [23]. The combination of ash dieback with the outbreaks of ash sawflies could acerbate even further the already precarious situation of the ash tree population in Ireland.…”
Section: Discussionmentioning
confidence: 99%
“…A combination effect of sunken canker with H. fraxineus further aggravates ash dieback, accelerating the decline of the tree (Linaldeddu et al 2020). All of the three species here described have not been formally recorded in Ireland yet (FRDBI database 2021) except by Lahiri, Murphy and Hodkinson (2021).…”
Section: Powdery Mildew (Phyllactinia Fraxini and P Fraxinicola)mentioning
confidence: 99%